Towards core-shell bifunctional catalyst particles for aqueous metal-air batteries: NiFe-layered double hydroxide nanoparticle coatings on γ-MnO2 microparticles - Flegler, Andreas; Muessig, Stephan; Prieschl, Johannes; Mandel, Karl; Sextl, Gerhard (Electrochimica Acta, 2017)
Herein, we investigated the synthesis of a bifunctional catalyst particle system for aqueous metal-air batteries. To target a system which possesses both, oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) capabilities, γ-MnO2 microparticles were combined with NiFe layered double hydroxides (LDH) to a core-shell system. NiFe-LDH can be optimized in its constituency to yield a very low onset potential (at 10 mA cm−2) for the oxygen evolution reaction of only 569 mV vs. Hg/HgO. We investigated different coating processes (in-situ precipitation coating and sonochemical assisted coating) in order to create a bifunctional system of LDH shell@γ-MnO2 core. It was found that the overall catalytic functionality of the bifunctional system strongly depends on the coating process, as this ultimately determines the surface nature and thus the behavior in ORR and OER reactions, respectively, of this core-shell system.
CRIS-Team Scopus Importer:2020-04-02
Keywords: bifunctional catalyst; layered double hydroxides; metal-air batteries; NiFe LDH; OER